Attempts to induce nocardioform placentitis (Crossiela equi) experimentally in mares. (1st April 2014) - Canisso, I. F.; Ball, B. A.; Erol, E.; Claes, A.; Scoggin, K. E.; McDowell, K. J.; Williams, N. M.; Dorton, A. R.; Wolfsdorf, K. E.; Squires, E. L.; Troedsson, M. H. T.
Summary Reasons for performing study Nocardioform placentitis in horses is poorly understood, and the development of an experimental model would be of help in understanding the pathogenesis of the disease. Objectives To investigate whether (1) intrauterine inoculation of Crossiela equi during the periovulatory period or (2) i.v., oral or intranasopharyngeal inoculation of C. equi during midgestation would result in nocardioform placentitis, and (3) before and after mating endometrial swabs present evidence of nocardioform placentitis‐associated organisms (C. equi or Amycolatopsis spp.). Methods In Study I, mares (n = 20) received an intrauterine inoculation of C. equi 24 h after artificial insemination. Endometrial swabs were obtained 24 h post inoculation for PCR analysis. In Study II, pregnant mares (at 180–240 days of gestation) were inoculated with C. equi by intranasopharyngeal (n = 5), oral (n = 4) or i.v. (n = 4) routes. Sixty contemporaneous pregnant mares maintained on the same farm served as control animals. In Study III, privately owned Thoroughbred mares (n = 200) had endometrial swabs collected before and within 24–48 h after mating for detection of nocardioform microorganisms. Results In Study I, C.equi was identified by PCR in 3 of 20 mares following intrauterine inoculation. Pregnancy was established in 19 of 20 treated mares. There were 2 embryonic losses and one abortion at 177 days of gestation (undetermined cause). Sixteen mares delivered a normal foal and placenta. In Study II, one mare (oral inoculation) aborted at 200 days of gestation (unidentified cause). The remaining mares delivered a normal foal and placenta. In Study III, none of the mares yielded positive endometrial PCR for nocardioform microorganisms. Conclusions We were unable to induce nocardioform placentitis, and there was no evidence of nocardioform microorganisms in endometrial swabs of broodmares before or after mating. These findings suggest that nocardioform placentitis is not induced simply via the presence of nocardiform actinomycetes and that route, insufficient duration of exposure and dose may play a role in the development of disease. Additional predispositions may also be involved in the development of nocardioform placentitis.